2011
DOI: 10.1097/ta.0b013e31821957e3
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Surgically Treated Femur Fractures Associated With Long-Term Bisphosphonate Use

Abstract: BP-related fractures are a recently described phenomenon. Despite initial osteoporosis, the DEXA scan may appear outside the osteoporotic range for the femoral neck in these patients. In addition, a much higher failure rate with intramedullary nailing requiring revision surgery may occur with these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
3
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 26 publications
4
106
3
4
Order By: Relevance
“…Bisphosphonates have been proven to be highly effective as a treatment modality in patients with osteoporosis for the prevention of osteoporotic fractures [2,9,30]. Although the association between long-term bisphosphonate therapy and atypical femoral fractures is now accepted, the benefits of bisphosphonate therapy far outweigh the risks, and bisphosphonates continue to be a mainstay of treatment [1].…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates have been proven to be highly effective as a treatment modality in patients with osteoporosis for the prevention of osteoporotic fractures [2,9,30]. Although the association between long-term bisphosphonate therapy and atypical femoral fractures is now accepted, the benefits of bisphosphonate therapy far outweigh the risks, and bisphosphonates continue to be a mainstay of treatment [1].…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonate (BP) therapy has become the most widely used method for the treatment of osteoporosis [1][2][3][4]. BP therapy inhibits osteoclast-mediated bone resorption to prevent bone loss and to improve bone strength [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Atypical femoral fractures are usually atraumatic, may be bilateral, and may have delayed fracturehealing. [5,6,9] For this reason we discontinued alendronate treatment for our patients. They are now receiving only calcium and vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Also, recent reports have suggested that a potential complication may be delayed union after atypical femoral fracture stabilization in patients taking long-term bisphosphonate. [5,6] This article describes two patients on long-term alendronate therapy which were treated for atypical femoral fractures healed with surgical treatment plus calcium, vitamin D support, and alendronate discontinuation.…”
mentioning
confidence: 99%